2019
DOI: 10.2174/1871525717666191019162254
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Associated Factors among Chronic Heart Failure Clients on Follow Up Oromia Region, West Ethiopia

Abstract: Background: Chronic heart failure is a complex clinical syndrome with typical symptoms that can occur at rest or on effort. It requires patients to manage their lifestyle with their disease and when to notify their healthcare provider. The study was aimed to identify medication adherence and associated factors among chronic heart failure clients on follow up Oromia region, West Ethiopia, 2017. Methods: Institutional based cross-sectional study design was employed, after selecting three hospitals by lottery m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
4
3
0
1
Order By: Relevance
“…Participants who didn't add salt when cooking were 1.72 times more likely to have medication adherence than those who added salt to food when cooking. This study was consistent with a study done in West Ethiopia (30). This may be due to health consciousness and lifestyle factors.…”
Section: Medication Adherencesupporting
confidence: 93%
See 2 more Smart Citations
“…Participants who didn't add salt when cooking were 1.72 times more likely to have medication adherence than those who added salt to food when cooking. This study was consistent with a study done in West Ethiopia (30). This may be due to health consciousness and lifestyle factors.…”
Section: Medication Adherencesupporting
confidence: 93%
“…Self-care Behaviours Adherence Self-care involves behaviours such as taking medications, monitoring and interpreting symptoms, keeping appointments, and contacting health care providers when needed (19).…”
Section: Operational De Nition and De Nition Of Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a moderate but significant relationship was noted between self-care agency and treatment adherence. A similar result was reached by Fetensa et al (2019) in patients with coronary disease and by Velandia-Arias and Rivera-Álvarez (2009) in patients with hypertension. These results are reasonable considering that higher levels of self-care may be expected to translate into better therapeutic goal achievement and treatment adherence.…”
Section: Discussionsupporting
confidence: 77%
“…In Ethiopia, few published studies have reported the level of medication adherence among heart failure patients either separately [ 21 ] or as a part of drug therapy problems [ 22 ]. However, due to a variation in the study setting, the level of care, and sociodemographic characteristics such as language differences, the findings might be difficult to extrapolate to this study setting.…”
Section: Introductionmentioning
confidence: 99%